2018
DOI: 10.5194/acp-18-13495-2018
|View full text |Cite
|
Sign up to set email alerts
|

Snow scavenging and phase partitioning of nitrated and oxygenated aromatic hydrocarbons in polluted and remote environments in central Europe and the European Arctic

Abstract: Abstract. Nitrated and oxygenated polycyclic aromatic hydrocarbons (N/OPAHs) are emitted in combustion processes and formed in polluted air. Their environmental cycling through wet deposition has hardly been studied. Fresh snow samples at urban and rural sites in central Europe, as well as surface snow from a remote site in Svalbard, were analysed for 17 NPAHs, 8 OPAHs, and 11 nitrated mono-aromatic hydrocarbons (NMAHs), of which most N/OPAHs as well as nitrocatechols, nitrosalicylic acids, and 4-nitroguaiacol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 93 publications
(128 reference statements)
5
20
0
Order By: Relevance
“…These trends are in good agreement with other studies, where 4-NC, MNCs and 4-NP were the most abundant NMAHs (Kitanovski et al, 2012b;Chow et al, 2016). However, we previously found different concentration trends in snowscavenged atmospheric particles collected in MZ, where 4-NC and MNCs were the second most abundant NMAH species following NPs (Shahpoury et al, 2018). ∑NMAH winter concentrations at TK were higher than those found in winter PM2.5 and PM10 from Hong Kong (China; Chow et al, 2016) and rural Belgium (Kahnt et al, 2013), respectively, but lower than NMAH concentrations in winter PM10 samples from Ljubljana (Slovenia; Kitanovski et al, 2012b) MZ were among the lowest values reported so far (Iinuma et al, 2010;Kitanovski et al, 2012b;Kahnt et al, 2013;Mohr et al, 2013;Chow et al, 2016;Li et al, 2016;Teich et al, 2017;Wang et al, 2019).…”
Section: Levels Of Nmahssupporting
confidence: 92%
See 2 more Smart Citations
“…These trends are in good agreement with other studies, where 4-NC, MNCs and 4-NP were the most abundant NMAHs (Kitanovski et al, 2012b;Chow et al, 2016). However, we previously found different concentration trends in snowscavenged atmospheric particles collected in MZ, where 4-NC and MNCs were the second most abundant NMAH species following NPs (Shahpoury et al, 2018). ∑NMAH winter concentrations at TK were higher than those found in winter PM2.5 and PM10 from Hong Kong (China; Chow et al, 2016) and rural Belgium (Kahnt et al, 2013), respectively, but lower than NMAH concentrations in winter PM10 samples from Ljubljana (Slovenia; Kitanovski et al, 2012b) MZ were among the lowest values reported so far (Iinuma et al, 2010;Kitanovski et al, 2012b;Kahnt et al, 2013;Mohr et al, 2013;Chow et al, 2016;Li et al, 2016;Teich et al, 2017;Wang et al, 2019).…”
Section: Levels Of Nmahssupporting
confidence: 92%
“…N/OPAHs were extracted from PM samples following a QuEChERS method with slight modifications (Albinet et al, 2014;Shahpoury et al, 2018). Briefly, each filter paper was placed inside a glass centrifuge tube (Duran, Schott, Mainz, Germany) and spiked with a mixture of internal standards containing 60 ng of each 1-nitronaphthalene-d7, 2-nitrofluorene-d9, 9nitroanthracene-d9, 3-nitrofluoranthene-d9, 1-nitropyrene-d9, 6-nitrochrysene-d11, 9,10anthraquinone-d8, and 9-fluorenone-d8.…”
Section: Chemical Analysis Of Nitro-and Oxy-polycyclic Aromatic Hydromentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the PM 0.97 size fraction (Table S11), the correlation with K + was only significant for 1-NPYR at TK, whereas both BaOFLN and 1-NPYR correlated with WSOC and HULIS in this size fraction. 1-NPYR is the predominant congener among NPAHs found in diesel engine exhaust particles and was proposed as a tracer for diesel emission (Bamford et al, 2003;IARC, 2013), but it may also be emitted with relatively small quantities from biomass-fuelled combustion (Shen et al, 2012;Orakij et al, 2017). These findings suggest the importance of primary emission sources including BB and diesel exhaust in the TK study area.…”
Section: Concentrations and Sources Of Npahs And Opahsmentioning
confidence: 83%
“…Polycyclic aromatic hydrocarbons (PAHs) and their nitrated and oxygenated derivatives (NPAHs and OPAHs), as well as hydroxy derivatives (OH-PAHs), are ubiquitous in the atmosphere (Walgraeve et al, 2010;Lammel, 2015;Bandowe and Meusel, 2017;Shahpoury et al, 2018). They are primarily emitted from the incomplete combustion of fossil fuels (Zielinska et al, 2004;Karavalakis et al, 2010;Pham et al, 2013;Inomata et al, 2015) and wood, coal, and biomass burning (Ding et al, 2012;Shen et al, 2012Shen et al, , 2013aHuang et al, 2014;Vicente et al, 2016). The PAH derivatives are secondarily formed by the reaction of parent PAHs with atmospheric oxidants such as OH, NO x and O 3 .…”
Section: Introductionmentioning
confidence: 99%